Efficient wideband signals’ direction of arrival estimation method with unknown number of signals - Yaoping Zeng; Guangyue Lu (International Journal of Distributed Sensor Networks)
This article focuses on the direction of arrival estimation of wideband signals, and an efficient method based on test of orthogonality of frequency subspaces is proposed. Using suitable coefficient m to weight and inverse the covariance matrix, the proposed method can obtain estimated noise subspace with unknown number of signals. Unlike conventional subspace estimation with heavy complex computations, the proposed method reduces the amount of computation by real matrix multiplication, and through only half of the total angular field-of-view. It decreases the computational load of spectrum peak search to half. Moreover, compared with the existing real-valued techniques suitable for only the centro-symmetrical array, the new method can be applied to arbitrary array. The simulation and experimental data results are provided to demonstrate the effectiveness and performance of the proposed method.